Impact of body and orofacial appearance on life satisfaction among Brazilian adults - Campos, Lucas Arrais [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; da Silva, Wanderson Roberto [UNESP]; Peltomäki, Timo; dos Santos Pinto, Ary [UNESP]; Marôco, João (Public Library of Science (PLoS), 2022)
Aims 1. to elaborate a general model of physical appearance taking into account body image (BI) and orofacial appearance (OA) components; and 2. to evaluate the impact of BI and OA on life satisfaction among Brazilian adults. Methods This is a cross-sectional observational study. The cognitive, behavioral, affective, and satisfaction/ dissatisfaction aspects of BI, the satisfaction and psychosocial impact of OA, and life satisfaction were evaluated by self-reported psychometric scales. Principal Component Analysis and Parallel Analysis were performed. Structural equation models were elaborated to estimate the impact of BI and OA on life satisfaction. The fit of the models was verified and the significance of the path estimates (β) was evaluated using z-tests (α = 5%). Results A total of 1,940 individuals participated in the study (age: mean = 24.8, standard deviation = 5.7 years; females = 70.1%). In the male sample, three physical appearance factors were retained (OA, cognitive and behavioral components of BI, and affective and satisfaction/dissatisfaction components of BI). In the female sample, two factors were retained (OA and all components of BI). All factors had significant impact on life satisfaction (β = |0.26|-|0.48|, p<0.001) in both samples. Individuals dissatisfied with BI and OA had lower levels of life satisfaction. For men, the affective and satisfaction components of BI had a greater impact on life satisfaction (β = 0.48, p<0.001) than the other factors (β =] -0.30;-0.25[, p<0.001). For women, both BI and OA had a similar impact (BI: β = -0.30, p<0.001; OA: β = -0.32, p<0.001). Conclusion BI and OA formed distinct clusters in the physical appearance evaluation. Physical appearance was perceived differently by men and women, fostering discussion about the sociocultural construction of the body. BI and OA had a significant impact on life satisfaction and should be considered in assessment and treatment protocols.